Margaret Chase Smith Library 2015 Student Essay Contest: Xenophobia and Amnesty - Plourde, Taylor (Maine Policy Review, 2016)
Each year the Margaret Chase Smith Library sponsors an essay contest for high school seniors. In this issue, we feature the three prize-winning essays as the Margaret Chase Smith Essay. The 2015 essay prompt asked students to weigh in with their opinions about what current U.S. immigration policy should be in light of the historical backdrop of alternating cycles of welcome and wariness toward foreigners. In the third place prize-winning essay, Taylor Plourde describes the pattern of xenophobia that has often permeated American attitudes about immigrants. She discusses some of the ways forward to dealing with the current situation of immigrants who have come illegally into the country.